A study of the impact of digital financial inclusion on multidimensional food security in China - Tan, Yunshu; Cheng, Qiuwang; Ren, Xiaojin; Huang, Xiang; Chen, Qin; Zhang, Qiuyi (Frontiers in Sustainable Food Systems, 2024)
With frequent occurrences of global public events, the prices of national grains continue to soar. As one of the countries with the largest populations globally, China has always regarded food security as a fundamental cornerstone of its development. However, with the continuous emergence of factors such as urbanization, scarcity of land resources, and climate change, China’s food security faces unprecedented challenges. Hence, this study empirically examines the impact of digital inclusive finance on multi-dimensional food security based on panel data from 30 provinces in China from 2011–2020. The research found that China’s multi-dimensional food security level from 2011–2020 showed a stable yet rising trend, with the spatial pattern of each location generally consistent with the overall trend. The Theil index for China’s multi-dimensional food security showed an upward trend from 2011–2020. Digital inclusive finance can promote multi-dimensional food security. The breadth of coverage and depth of use of digital inclusive finance have a significant promoting effect on safeguarding multi-dimensional food security, while the degree of digitization has not played a promoting role. Digital inclusive finance mainly ensures multi-dimensional food security through two pathways: promoting urbanization levels and enhancing marketization levels.